Biochemical and mechanical environment cooperatively regulate skeletal muscle regeneration - Calve, Sarah (Federation of American Societies for Experimental Biology, 2012)
During forelimb regeneration in the newt Notophthalmus viridescens, the dynamic expression of a transitional matrix rich in hyaluronic acid, tenascin-C, and fibronectin controls muscle cell behavior in vivo and in vitro. However, the influence of extracellular matrix (ECM) remodeling on tissue stiffness and the cellular response to mechanical variations during regeneration was unknown. By measuring the transverse stiffness of tissues in situ, we found undifferentiated regenerative blastemas were less stiff than differentiated stump muscle (13.3±1.6 vs. 16.6±1.2 kPa). To directly determine how ECM and stiffness combine to affect skeletal muscle fragmentation, migration, and fusion, we coated silicone-based substrates ranging from 2 to 100 kPa with matrices representative of transitional (tenascin-C and fibronectin) and differentiated environments (laminin and Matrigel). Using live-cell imaging, we found softer tenascin-C-coated substrates significantly enhanced migration and fragmentation of primary newt muscle cells. In contrast, stiffer substrates coated with laminin, Matrigel, or fibronectin increased differentiation while suppressing migration and fragmentation. These data support our in vivo observations that a transitional matrix of reduced stiffness regulates muscle plasticity and progenitor cell recruitment into the regenerative blastema. These new findings will enable the determination of how biochemical and mechanical cues from the ECM control genetic pathways that drive regeneration.—Calve, S., Simon, H.-G. Biochemical and mechanical environment cooperatively regulate skeletal muscle regeneration.